Efficiency Analysis of East European Electricity Distribution in Transition: Legacy of the Past? - Astrid Cullmann; Jürgen Apfelbeck; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper provides a cross-country efficiency analysis of electricity distribution companies in East European transition countries (Poland, Czech Republic, Slovakia and Hungary). We compare the relative technical efficiency of East European regional distribution companies (RDCs) among themselves, as well as with German RDCs. We use the nonparametric DEA, and also apply bootstrapping techniques and the FDH-estimator; in addition, we carry out parametric analyses, mainly SFA (stochastic frontier analysis) and COLS (corrected ordinary least squares). The results suggest that the Polish distribution companies are still inefficiently small. The Czech Republic and Slovakia feature the highest efficiency.
Keywords: P31; L51; C67; C14; 330; Efficiency analysis; econometric methods; electricity distribution; transition; Eastern Europe